Digitizing Village Governance Through the SIGAP System to Accelerate Public Services and Development in Aceh - Helmi, Helmi; Nofriadi, Nofriadi; Hasan, Effendi; Agustina, Soraya; Abdillah, Arif (Department of Government Studies, Universitas Syiah Kuala, 2025)
This research focuses on the digitalization of villages through one of the Aceh government policies, namely the implementation of the SIGAP application in each village pioneered by the Community Empowerment Office and Village. This research aims to answer the problems of service and development as well as the urgency of implementing SIGAP in realizing digitalization-based village governance and accelerating digital-based development. This research uses qualitative methods on collecting, analyzing and processing data based on the Creswell model. The data collection techniques are carried out through, observation, FGD and interviews with data validity and data processing. The findings in this study show that the digitalization of village governance in improving services and accelerating development through the SIGAP application is declared to have a positive impact and have a very significant influence on the village government and the community. Through this research, it is also known that SIGAP plays an important role in facilitating data accessibility and accountability of the Village government through the features contained in the SIGAP application. So it is concluded that SIGAP is the right solution in accelerating digital-based services and development in villages.